A Hand Surgeon's Guide to Common Onychodystrophies. (March 2014) - Fowler, John R.; Stern, Elisha; English, Joseph C.; Goitz, Robert J.
The human fingernail contributes to the precise dexterity of the fingers, enhances sensibility, allows manipulation of fine objects, and shields the fingertip from traumatic injury. Nail abnormalities are a common incidental finding in the course of a hand surgeon's daily practice. These abnormalities may be clues to systemic, dermatologic, traumatic, and infectious processes that would benefit from further evaluation and treatment. The purpose of this review is to discuss common nail dystrophies and their related diagnoses.